KREATIFITAS DAN INOVASI PRODUK IKAN ASAP BERBASIS DIGITAL DI NEGERI HATIVE KECIL KOTA AMBON - Nanlohy, Hellen; Gaspersz, Febe F; Anaktototy, Yofita; Moa, Petrus (Pattimura University, 2022)
Business opportunities for women as entrepreneurs have opened up job opportunities to be able to improve the family economy. Community Service activities for smoked skipjack tuna entrepreneurs in Hative Country aim to increase their knowledge of business management, good and correct fish smoking as well as making packaging and branding as well as conducting digital marketing. The methods used in this activity are counseling and training. The result of this activity is that entrepreneurs understand about good business management, good fish smoking methods, and are very interested in digital marketing